2014
DOI: 10.3892/ol.2014.2411
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutational concordance between primary and metastatic colorectal adenocarcinoma

Abstract: KRAS mutation analysis is commonly performed on tissue samples obtained from primary colorectal cancers (CRCs). The metastatic lesions of CRC are usually considered as qualitatively similar or even identical to the primary tumors. The aim of this study was to evaluate the spectrum and distribution of KRAS mutations in a large collection of CRCs, while also evaluating the concordance of primary and metastatic lesions among available paired specimens from the same patients. A total of 729 patients with histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
17
2
Order By: Relevance
“…For example, Siyar Ekinci et al found that the KRAS mutation rate is inconsistent between liver or lung metastases and primary tumors; both the primary tumor mutant and paired metastases wild-type also have primary tumor wild-type and paired metastases mutant 21,23. Moreover, KRAS gene consistency has been reported between primary tumors and metastases, especially non-metastatic LNs 16. In our study, the KRAS gene status was not consistent between primary tumors and LN metastases but identical between primary tumors and liver or lung metastases.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, Siyar Ekinci et al found that the KRAS mutation rate is inconsistent between liver or lung metastases and primary tumors; both the primary tumor mutant and paired metastases wild-type also have primary tumor wild-type and paired metastases mutant 21,23. Moreover, KRAS gene consistency has been reported between primary tumors and metastases, especially non-metastatic LNs 16. In our study, the KRAS gene status was not consistent between primary tumors and LN metastases but identical between primary tumors and liver or lung metastases.…”
Section: Discussioncontrasting
confidence: 55%
“…Mutation status concordance was reported in 43 studies for KRAS 4 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 , in 16 studies for BRAF 7 13 14 15 16 17 18 24 25 26 27 33 34 41 43 48 , in 9 studies for PIK3CA 13 14 15 18 25 27 34 48 49 and in 8 studies for PTEN 7 13 17 31 32 34 47 48 . The majority of studies (40/43) tested the KRAS mutations on codons 12 and 13 4 7 8 …”
Section: Resultsmentioning
confidence: 74%
“…Searching of ASCO did not identify any further eligible studies, while reference list checking of reviews and included studies identified 2 additional studies. In total, 46 relevant studies 4 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 were identified. Details are presented in figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS mutation is recognized as an early event in colorectal carcinogenesis (20,21). Therefore, concordance of KRAS mutation status between primary CRC and corresponding metastases should be expected, and previous studies demonstrated high concordance rate (22)(23)(24). Nevertheless, some other studies reported discordance of KRAS mutation status between primary CRC and corresponding metastases.…”
Section: High Concordance Rate Of Kras/braf Mutations and Msi-h Betwementioning
confidence: 97%